Rewriting Ancient Geography. - Caballero-Sánchez, Paula María (Routledge, 2025)
The chapter provides a comprehensive chronological overview of the rewriting of ancient geographical texts by Byzantine professors, with an emphasis on academic geography, while also addressing political and astronomical/mathematical geography. It begins with the Macedonian era with Photios (9th cent.), continues through the mid-Byzantine period presenting the contributions of eminent professors and scholars of the time, and concludes with an examination of the rewriting work carried out by eminent professors and scholars of the Palaiologan era, culminating in the last years of the Empire, with Georges Gemistos Plethon (15th cent.).
https://authorservices.taylorandfrancis.com/frequently-asked-questions/open-access-books-faq/?srsltid=AfmBOopZcHnD5qpvo_xCpqAYD-O3CMuS46bI9Z6UEXcTyq8iFJzZNVQA
Keywords: Geografía antigua; Imperio bizantino - Civilización; Saber y erudición - Imperio bizantino; Byzantine scholarship; Ancient geography; Rewriting; Manuscripts